Development of Artificial Intelligence-Based Learning Videos on the Topics of Air Pollution using Lumen App - Romundza, Febbry; Harizon, Harizon; Miharti, Isra; Novferma, Novferma (FKIP Universitas Lampung, 2023)
Abstract: This research is a development research that aims to produce multimedia-based learning media that is valid, effective and practical. This research uses programming (AI) and is combined with the Lumen application. The development model of this research is: ADDIE development, namely analysis, design, development, implementation, evaluation. The subjects of this study were seventh semester students of environmental chemistry courses on air pollution material. There are three data collection techniques carried out in this study, namely validity, obtained through validation by validators; effectiveness, obtained through learning outcomes and student responses to learning media; practicality, obtained from assessment instruments by validators. The results showed that the average value of validity was 86.2%. The effectiveness of the media from student learning outcomes obtained an average of 86.3%. The practicality of the learning video was obtained from the questionnaire assessment of lecturers and students with an average practicality value of 89%. Keywords: learning video, artificial intelligence, addie model, lumen's app or phrase. Abstrak: Penelitian ini merupakan penelitian pengembangan bertujuan untuk menghasilkan media pembelajaran berbasis multimedia yang valid, efektif dan praktis. Penelitian ini menggunakan pemrograman (AI) dan dikombinasikan dengan aplikasi Steve Model pengembangan penelitian ini yaitu : pengembangan ADDIE, yaitu analysis, design, development, implementation, evaluation. Subjek penelitian ini adalah mahasiswa semester tujuh mata kuliah kimia lingkungan pada materi polusi udara. Teknik pengumpulan data yang dilakukan pada penelitian ini ada tiga yaitu kevalidan, diperoleh melalui validasi oleh validator; keefektifan, diperoleh melalui hasil belajar dan respon mahasiswa terhadap media pembelajaran; kepraktisan, diperoleh dari instrumen penilaian oleh validator. Hasil penelitian menunjukkan bahwa nilai rata-rata kevalidan yaitu 86,2%. Keefektifan media dari hasil belajar mahasiswa memperoleh rata-rata sebesar 92,3%. Kepraktisan video pembelajaran diperoleh dari penilaiaan angket dosen dan mahasiswa dengan nilai rata-rata kepraktisan 89%. Kata kunci: video pembelajaran, artificial intelligence, model addie, aplikasi lumen DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp801-809